The proinflammatory effect of C-reactive protein on human endothelial cells depends on the Fc?RIIa genotype - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Klinghammer, Lutz; Stumpf, Christian; Achenbach, Stephan; Herrmann, Martin; Reis, André; Garlichs, Christoph (Thrombosis Research, 2014)
The stimulatory effects of CRP (C-reactive protein) on endothelial cells are mainly mediated via Fc?RIIa. This receptor exists in two different allotypes bearing either arginine (R131) or histidine (H131) at the extracellular amino acid position 131 of the mature protein, but only Fc?RIIa-R131 displays high avidity for CRP. This study investigated the role of the Fc?RIIa genotype in CRP-stimulated endothelial cells.We tested the effects of CRP on expression of the adhesion molecules ICAM-1, VCAM-1, and E-selectin, as well as the endothelial release of pro-inflammatory molecules as a function of the Fc?RIIa-genotype (Fc?RIIa-H/H131, Fc?RIIa-H/R131, Fc?RIIa-R/R131) in HUVEC (Human Umbilical Vein Endothelial Cells). HUVEC were grouped according to their Fc?RIIa status by genotyping with an allele specific nested-PCR. The expression of ICAM-1, VCAM-1, and E-selectin on HUVEC was detected by flow cytometry. The release of soluble markers (sCD40L, IL-6, IL-8, MCP-1, tPA, sP-selectin, and sVCAM-1) was measured using a multiplex assay for flow cytometry.CRP-stimulated expression of ICAM-1 and E-selectin was dependent on the specific Fc?RIIa-genotype, with most pronounced induction in HUVEC with the Fc?RIIa-R/R genotype, followed by H/R and H/H. In accordance with this finding, the supernatants of stimulated HUVEC with the R/R genotype showed significantly higher levels of tPA, MCP-1, and IL-6. Our data show that CRP stimulates the expression of adhesion molecules and the release of soluble markers by HUVEC as a function of the Fc?RIIa-genotype. These findings could be relevant in the context of risk stratification in patients with cardiovascular disease.
EVALuna2:9209